The Challenges of Dignifying Bahasa Indonesia in the Bali Tourism Area - I Made Suparta; I Wayan Mawa (Eastasouth Institute, 2025)
The elevation of the Bahasa Indonesia as the national language in public spaces faces serious challenges, particularly in international tourism areas such as Bali. This study aims to identify and analyze the various challenges hindering the optimal use of Bahasa Indonesia in Bali’s tourism sphere. The research employs a descriptive qualitative approach using data collected through field observation, interviews with tourism stakeholders, and documentation of language use in public media. The findings reveal a dominant use of foreign languages in signage, restaurant menus, and tourism promotions, illustrating the diminishing presence of Bahasa Indonesia in public domains. Economic factors, global market demands, limited linguistic supervision, and low awareness among tourism actors regarding language regulations are key contributing issues. Nevertheless, strategic opportunities exist through local government policy, enhanced roles of the Language Agency, and community empowerment to reintegrate Bahasa Indonesia into the tourism ecosystem. The study recommends inclusive language education, regular language audits, and cross-sector collaboration to reinforce national identity through language amid globalizing forces.